Integrated barrier stick for reserved parking / Siti Nor Azmah Adam - Adam, Siti Nor Azmah (Faculty of Information Technology and Quantitative Sciences, 2006)
Parking is a common problem that happened anywhere. Apartments, flats, hospitals are the most examples place where this problem always occurred. Even the parking space status is reserved which mean it is owned by somebody or the owner already paid for the parking space, it is still not ensure that when they come back home they can park at their reserved parking. May be somebody already take place with the common reason, just want to park for a few minutes. But it will burden the parking owners. For their rights, they have to report to maintenance office and the illegal park users’ car will be clamp. Another way to restrict from be parked illegally is by put a cone on the reserved parking. But it stills not a good way because somebody can just put the cone at the end of parking space or somewhere and park their car there. So, as one of the solutions for this problem is develop an integrated barrier stick for reserved parking. This project is focusing on the design and implementation to help users or parking owners to restrict other people from using their reserved parking space. The project involved the integration of infrared remote control where the infrared receiver circuit will be build in the stick and link to the motor which can move ninety degrees up and down. The stick will be work when it received signal from the infrared remote control. The signal received by the receiver which then transmits it to the motor to make a movement whether to turn up or turn down. When the parking owner wants to park their car, they just press a button on the remote and the integrated barrier stick will turn down. If they want to leave their parking space, they also just have to press again a button on the remote and the integrated barrier stick will turn up. So, nobody can park their car illegally.